Online Learning Based on the 5E Learning Cycle: Effects on Conceptual Understanding and Science Process Skills in Colligative Properties of Solutions: - Rody Putra Sartika; Masriani Masriani; Hairida Hairida; Lukman Hadi; Vidya Setyaningrum; Natalino Pereira Parada (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Difficulties in understanding abstract chemistry concepts, particularly colligative properties of solutions, remain a major problem in online learning environments, where students often demonstrate limited conceptual understanding and underdeveloped science process skills (SPS). This study aims to examine the effectiveness of online learning based on the 5E learning cycle model in improving students’ conceptual understanding and SPS, as well as to analyze the relationship between these variables. This research employed a quantitative approach using a one-group pretest–posttest pre-experimental design. The research participants were 38 students from the Chemistry Education Study Program at Tanjungpura University, selected through saturation sampling. Data were collected using a conceptual understanding test and an  SPS test, and were analyzed using inferential statistical tests and descriptive analysis with the assistance of SPSS software. The results showed a statistically significant difference in students’ conceptual understanding before and after the learning intervention (p < 0.05), although the normalized gain was categorized as low. Students’ SPS were generally in the good category, despite several aspects requiring improvement. Furthermore, the results of the Spearman correlation test indicated a significant positive relationship between conceptual understanding and SPS (p < 0.05), with a moderate level of correlation. These findings indicate that the 5E learning cycle model in online learning has the potential to support conceptual understanding and SPS, although additional instructional support is needed to optimize learning outcomes